Comparative Study of E- and U-core Modular Dual-Stator Axial-Field Flux-Switching Permanent Magnet Motors With Different Stator/Rotor-Pole Combinations Based on Flux Modulation Principle - Shuai Wang; Keman Lin; Mingyao Lin; Yong Kong; Da Xu; Nian Li; Peng Wang (IEEE Access, 2021)
In this paper, the dual-stator axial-field flux-switching permanent magnet (DSAFFSPM) motors with E- and U-core stator modular segments, as well as different stator/rotor-pole combinations are compared. The operation performance of the DSAFFSPM machines are explored by using the MMF-permeance model method. A more comprehensive theoretical analysis, no more limited to numerical calculation, is presented. This reveals directly the relations between the operation performance and design parameters of the machine. The performance comparisons between the E-shaped and U-shaped teeth DSAFFSPM machines are given, including the effects of the structural parameters on the electromagnetic torque, different stator/rotor-pole combinations on the winding factor and gear ratio, the differences of the average torque and the torque density and the efficiency in the 12/10 U-core and 6/10 E-core topology. These are the basis of the DSAFFSPM machine design and optimization. Finally, the experiments on the two prototype, 6/10 E-core and 12/10 U-core DSAFFSPM machines are carried out. The results show that the average torque of the 12/10 U-core prototype is higher than that of the 6/10 E-core prototype, while the torque density and the efficiency of 6/10 E-core DSAFFSPM machines are much higher.